The decomposition method applied to solve high-order linear Volterra-Fredholm integro-differential equations - El-Sayed, SM; Kaya, D; Zarea, S (Walter de Gruyter Gmbh, 2004)
In this paper, Adomian's decomposition method is applied to solving high-order linear Volterra-Fredholm integro-differential equations. Comparison with the results obtained in terms of Taylor's polynomials reveals that the Adomian's decomposition method is more accurate and is more efficient than the Taylor's expansion technique. The decomposition method also minimizes the computational difficulties of Taylor's expansion approach in that the components of the decomposition series are determined elegantly by using simple integrals.
Keywords: high-order linear Volterra-Fredholm integro-differential equations; Adomian's decomposition method; Adomian's polynomials; Taylor's expansion method